Lousy Revolutionaries: Fiction, Feminism, and Failure in Ilene Segalove's The Riot Tapes (1984) - Bradnock, Lucy E. (Oxford University Press, 2019)
In 1970, Ilene Segalove was a student at the University of California, Santa Barbara, during a period of violent protests against the American Vietnam War. In 1984, as Ronald Reagan was elected to his second term as US President, Segalove made a video art work entitled The Riot Tapes, which re-enacts those student days via the visual vocabulary of popular television. This article explores The Riot Tapes in the context of televised politics and the deployment of national and geopolitical historical narratives of conflict and protest. Drawing on Lauren Berlant’s delineation of ‘the female complaint’ (1988) and Hayden White’s ‘practical past’ (2014), I argue that in the video Segalove performs the position of failure, both in her quasi-autobiographical narrative of the “lousy revolutionary” and in her adoption of cultural genres historically deemed trivial and subordinate. She does so, I contend, in order to critique the gendered rhetoric of protest narratives, to resist the co-option of history in the era of the “televised presidency”, and to reclaim affect and ambivalence as viable modes of resistance.